2015
DOI: 10.1111/jnc.13179
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microglial activation contributes to propofol‐induced protection against post‐cardiac arrest brain injury in rats

Abstract: It has been suggested that propofol can modulate microglial activity and hence may have potential roles against neuroinflammation following brain ischemic insult. However, whether and how propofol can inhibit post-cardiac arrest brain injury via inhibition of microglia activation remains unclear. A rat model of asphyxia cardiac arrest (CA) was created followed by cardiopulmonary resuscitation. CA induced marked microglial activation in the hippocampal CA1 region, revealed by increased OX42 and P2 class of puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 54 publications
3
27
0
Order By: Relevance
“…The broad-spectrum tetracycline antibiotic, minocycline, is a known microglia activation inhibitor (Wang W. et al, 2015), with inhibitory action on P2X4 and P2X7 receptors (Stebbing, unpublished observations). To further explore its mechanisms of action on purinergic receptor activation and Ca 2+ homeostasis, we performed two-photon Ca 2+ fluorescence experiments in the presence of 0.1 mM minocycline and varying ATP concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The broad-spectrum tetracycline antibiotic, minocycline, is a known microglia activation inhibitor (Wang W. et al, 2015), with inhibitory action on P2X4 and P2X7 receptors (Stebbing, unpublished observations). To further explore its mechanisms of action on purinergic receptor activation and Ca 2+ homeostasis, we performed two-photon Ca 2+ fluorescence experiments in the presence of 0.1 mM minocycline and varying ATP concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…; Wang et al . ), which then induce the dysfunction of serotoninergic neurons in the RVM. These results, together with those of other studies, indicate that cytokines and ROS subsequent to P2X7R activation in microglia can increase the activity of the pain facilitatory ON cells that express 5‐HT in the RVM by changing the environment in which these neurons live and promoting 5‐HT release into the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…P2X7R agonist, the NADPH oxidase activator, or IL-1b induced 5-HT release in the spinal dorsal horn. It was demonstrated that P2X7R activation in microglia triggers the release of proinflammatory mediators, namely, interleukin 1 (IL-1), TNF-a, and ROS (Solle et al 2001;Kim et al 2007;Sperlagh et al 2007;Ying et al 2014;Wang et al 2015), which then induce the dysfunction of serotoninergic neurons in the RVM. These results, together with those of other studies, indicate that cytokines and ROS subsequent to P2X7R activation in microglia can increase the activity of the pain facilitatory ON cells that express 5-HT in the RVM by changing the environment in which these neurons live and promoting 5-HT release into the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, ketamine is protective against ischemia in vitro as well [103], suggesting potential temperature independent effects. Propofol decreases CMR and CBF, but also offers other properties including mitigation of oxidative and excitotoxic stress [104, 105], apoptosis [106], inflammation [107], and autophagy [108]. Results of preclinical efficacy studies have been mixed.…”
Section: Ischemic Outcomementioning
confidence: 99%